Alcohol Mixed With Energy Drinks (AmED): A Perfect Recipe For Disaster. An Analysis Of AmED Consumption And Potential Health Effects - Cisowska, Zuzanna; Zdych, Martyna; Chudzik, Patrycja; Bodziony, Maksym; Terebus, Andrzej; Gaweł-Dąbrowska, Dagmara (Quality in Sport, 2025)
<div class="html-div xdj266r x11i5rnm xat24cr x1mh8g0r x14ctfv x1okitfd x6ikm8r x10wlt62 xerhiuh x1pn3fxy x12xxe5f x1szedp3 x1n2onr6 x1vjfegm x1k4qllp x1mzt3pk x13faqbe x1xr0vuk x1jm4cbz x1lmq8lz xrrpcnn x1xtl47e x13fuv20 xu3j5b3 x1q0q8m5 x26u7qi x19livfd x2t687o x3p3xfz x5od304 xp5s12f x11ucwad xgtuqic x155c047" role="presentation"> Introduction and purpose of research With the surge of popularity of energy drinks, a growing trend of mixing alcohol with energy drinks (AmED) has been observed, particularly among youth and young adults. This review aims to explore both the mechanism of action of this mixture as well as its short- and long-term effects. Research Materials and Methods A literature review was conducted using the PubMed database to identify studies on the health effects of alcohol mixed with energy drinks. The search included keywords such as “alcohol mixed with energy drinks”, "alcohol AND energy drinks" and "AmED AND health effects". Basic results Studies consistently report an association between AmED consumption and an increased risk of cardiovascular, mental, and kidney diseases, binge drinking and risky behaviors more frequently than those who consume alcohol alone. A common effect among AmED consumers is “false sobriety”, a phenomenon where individuals feel less intoxicated despite consuming high amounts of alcohol. However, due to the limited number of controlled human studies, the precise physiological and molecular interactions between caffeine and alcohol still remain unclear. Conclusions The ban on pre-mixed AmED products has not yet yielded satisfactory results. Therefore, governments should explore alternative measures, such as stricter regulations on marketing and sales or public awareness campaigns. This article highlights the issue of mixing alcohol with energy drinks, examining physiological effects, potential health risks, and broader societal impacts. With the growing popularity of this practice, our study emphasizes the need for continued research to guide effective prevention strategies and public health actions.